The run for personalized oncological therapy in pancreatic cancer: are we catching up with other tumors? - Molinari, Michele (Therapeutic Radiology and Oncology, 2018)
The most common type of pancreatic cancers (PC) originates from the ductal cells of the exocrine gland and belongs to the family of adenocarcinomas of the gastrointestinal tract (1-3).